The Adventures of Ook and Gluk: Kung Fu Cavemen from the Future (Captain Underpants) - George Beard and Harold Hutchins
Meet Ook and Gluk, the stars of this sensationally silly graphic novel from the creators of Captain Underpants! It's 500,001 BC, and Ook and Gluk's hometown of Caveland, Ohio, is under attack by an evil corporation from the future. When Ook, Gluk, and their little dinosaur pal Lily are pulled through a time portal to 2222, they discover a future world that's even more devastated than their own. Luckily, they find a friend in Master Wong, a martial arts instructor who trains them in the ways of kung fu. Now all they have to do is travel back in time 502,223 years and save the day!